2014
DOI: 10.1051/shsconf/20141201039
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Health and Income in Malaysia

Abstract: Abstract. This study employed the ARDL bounds test and Granger causality test to investigate long-and the short-run relationships among economic development, tourism sector development, and health care sector development in Malaysia. Annual time series data from 1981-2011 also were employed in this study. Based on our tests, there is a long-run relationship from economic development to health care sector development and from tourism development to health care sector development..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…Health system quality depicts the well-managed and well-facilitated health system of the country. Our results are in line with those of Ozturk [ 100 ] and Cheah and Abdul-Rahim [ 101 ], who also reported a positive and significant, impact of health expenditures per capita on tourism. Lee [ 102 ] also found a long-term positive relationship between health care and international tourism.…”
Section: Discussionsupporting
confidence: 93%
“…Health system quality depicts the well-managed and well-facilitated health system of the country. Our results are in line with those of Ozturk [ 100 ] and Cheah and Abdul-Rahim [ 101 ], who also reported a positive and significant, impact of health expenditures per capita on tourism. Lee [ 102 ] also found a long-term positive relationship between health care and international tourism.…”
Section: Discussionsupporting
confidence: 93%
“…In a different study, Lee (2010) discussed the relationship between health and international tourism and found a positive relationship between health and international tourism in the long term. Cheah and Abdul-Rahim (2014) examined the relationship between tourism development and health expenditures and found a positive relationship between the development of tourism and health expenditures. Shahbaz et al (2016) discussed the relationship between health expenditures, welfare level, and tourism revenues and concluded that there is a mutual causality relationship between these variables.…”
mentioning
confidence: 99%